Evaluasi Pengalaman Pengguna Aplikasi Hiip Indonesia Menggunakan Metode USE Questionnaire dan Usability Testing: Studi Kasus pada PT. Hiip Inovasi Indonesia - Novariany, Rani; Kusuma, Rahma Djati (LPPM IBI Kesatuan, 2023)
With the rapid development of mobile applications, user experience has become crucial in ensuring success and user satisfaction. This research paper presents an evaluation of the user experience of the Hiip Indonesia application, with a focus on usability assessment and user satisfaction. The research methodology employs two main methods: the USE Questionnaire and Usability Testing. The USE Questionnaire is a validated and widely used tool for assessing user satisfaction, while Usability Testing involves observing user interactions with the application and collecting qualitative and quantitative data. The research findings indicate that the usability level of the Hiip Indonesia application falls into the